A method for preparing ester

By using a multiphase supported silicon oxide-indium oxide catalyst to carry out alcohol dehydrogenation reaction in a fixed bed reactor, the problems of existing catalyst toxicity and low conversion rate are solved, and efficient, safe and environmentally friendly preparation of ethyl acetate with high selectivity and conversion rate are achieved.

CN116162024BActive Publication Date: 2025-04-18DALIAN INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111401154.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-24
Publication Date
2025-04-18
Estimated Expiration
2041-11-24

AI Technical Summary

Technical Problem

The existing catalysts for preparing ethyl acetate by dehydrogenation of ethanol have problems such as toxicity or low ethanol conversion, which is difficult to meet the production needs of high efficiency, safety and environmental protection.

Method used

The dehydrogenation reaction of alcohol is achieved by using a multiphase supported silicon oxide-indium oxide catalyst by filling the catalyst in a fixed bed reactor and controlling the reaction conditions such as temperature and space velocity. The catalyst consists of active metal, silicon oxide, indium oxide and catalyst aid. The particle size of indium oxide particles is controlled through the physical isolation of silicon oxide to improve catalytic activity and selectivity.

Benefits of technology

The preparation of ethyl acetate with high selectivity (up to 96%) and high conversion (up to 80%) is achieved, and the catalyst is non-toxic, has good stability, long life, and meets environmentally friendly and safe production requirements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003371523590000151
    Figure BDA0003371523590000151
  • Figure BDA0003371523590000161
    Figure BDA0003371523590000161
Patent Text Reader

Abstract

The present invention relates to a method for preparing an ester. The method uses alcohol as a reactant and prepares the corresponding ester by an oxygen-free dehydrogenation condensation reaction under the catalytic action of a supported silicon oxide-indium oxide composite catalyst. The reaction conditions are as follows: the reaction is carried out in a fixed bed reactor under normal pressure, the reaction temperature is 220-300°C, and the alcohol feed mass space velocity is 1.0-3.0h ‑1 The method is characterized in that a multiphase supported silicon oxide-indium oxide composite material is used as a catalyst, the catalyst is easy to prepare and catalyzes highly selective dehydrogenation condensation of alcohols while co-producing hydrogen. The conversion rate of alcohols reaches 80%, the highest selectivity of esters can reach 96%, and the catalyst has good stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing an ester, and in particular to a method for preparing an ester compound by using alcohol as a reactant through an oxygen-free dehydrogenation condensation process. Background Art

[0002] Ester compounds are important chemicals. Low molecular weight esters can be used as solvents, and esters with larger molecular weight are good plasticizers. Esters formed by alcohols with branched chains are excellent lubricants. Esters can also be used in industries such as spices, flavors, cosmetics, soaps and medicines. Among them: ethyl acetate is one of the most widely used fatty acid esters. It has excellent solubility properties and is a fast-drying, important green industrial solvent. It is widely used in the production of chemical products such as acetate fiber, ethyl fiber, chlorinated rubber, vinyl resin, synthetic rubber, coatings and paints; as an industrial solvent, it is used in coatings, adhesives, ethyl cellulose, artificial leather, linoleum colorants and artificial fibers; as an adhesive, it is used in the production of printing inks and artificial pearls; as an extractant, it is used in the production of products such as medicines and organic acids; as a spice raw material, it is the main raw material for fruit flavors such as pineapple, banana and strawberry, and spices such as whiskey and cream.

[0003] The production method of esters is still mainly based on the traditional esterification method. At present, large domestic methanol carbonyl acetic acid synthesis enterprises or enterprises with bioethanol equipment provide abundant and cheap acetic acid and ethanol raw materials, but the esterification process still has many disadvantages such as low utilization rate of acetic acid and environmental unfriendliness. Although the production process is relatively mature, the technical threshold is low, and the process and production technology are stable, the existing technology is increasingly unable to meet the needs from the perspective of market demand and the interests of manufacturers. Therefore, it is of practical significance to develop an ethyl acetate production process with high efficiency, energy saving and low environmental load, and it can also be effectively used for the preparation of other ester compounds. The route of preparing ethyl acetate by ethanol dehydrogenation condensation is highly economical and environmentally friendly, and is an ideal route for preparing ethyl acetate. The ethanol dehydrogenation condensation method uses ethanol as raw material and synthesizes ethyl acetate by one-step dehydrogenation through gas-solid phase reaction. It has the advantages of simple process, green process, and easy separation of product and catalyst. In 2001, Davy Company used toxic copper-chromium catalyst to carry out the reaction of ethanol dehydrogenation condensation to prepare ethyl acetate. The selectivity of ethyl acetate was about 94%, but the ethanol conversion rate was only about 27%. The copper-zinc-aluminum-zirconium catalyst used by Japan National Petroleum Corporation has an ethyl acetate selectivity of 90-95%, but an ethanol conversion rate of 45%.

[0004] Although the above catalysts achieve the production of ethyl acetate by dehydrogenation condensation of ethanol, the catalysts used are either toxic or have low ethanol conversion rates. Therefore, it is of great significance to develop a non-toxic, easily available, highly reactive and selective solid catalyst system. Summary of the invention

[0005] The significance of the invention is that it overcomes the shortcomings of the current process of preparing ethyl acetate by direct dehydrogenation condensation of ethanol. The preparation method has a simple reaction process, a non-toxic catalyst, high selectivity for ethyl acetate, good stability and long life.

[0006] The ethyl acetate involved in the present invention is prepared by the following scheme.

[0007] Alcohol is used as a raw material, and a reaction is carried out in a fixed bed reactor. After a multiphase supported silicon oxide-indium oxide catalyst is filled in a reaction tube, the reaction tube is placed in the fixed bed reactor, and the reaction temperature is 220-300° C. The multiphase supported silicon oxide-indium oxide catalyst is composed of active metal, silicon oxide, indium oxide and a catalyst promoter; the active metal in the multiphase supported silicon oxide-indium oxide catalyst is one, two or more of Cu, Fe, Zn, Ni, Ru, Pd, Pt and Au; the catalyst promoter in the multiphase supported silicon oxide-indium oxide catalyst can be one, two or more of Zr, La, Ce, Pr, Y, Mg, Ca, Ba and Al; the active metal content in the multiphase supported silicon oxide-indium oxide catalyst is 1.5%-10% (by weight); the indium oxide content is 10-35%; the catalyst promoter content is ≤10% (by weight). The preparation of the supported silicon oxide-indium oxide composite catalyst and the silicon oxide-cerium oxide carrier adopts the co-hydrolysis method of organosilane or tetraethyl orthosilicate and indium precursor salt, the hydrolysis is carried out at room temperature, the concentration of indium salt is 0.1-1.1 mol / L; the concentration of organosilane or tetraethyl orthosilicate is: 1-10 mol / L; the pH is: 8-11; the introduction of active metals and additives adopts the impregnation method. The alcohol can be aliphatic alcohol, aromatic alcohol, heterocyclic alcohol, diol and polyol; the feed mass space velocity of alcohol is 1.0-3.0h-1. The alcohol can be one, two or more of ethanol, propanol, butanol, pentanol, n-hexanol, heptanol and octanol; the feed mass space velocity of alcohol is 0.5-3.5h-1; the feed mass space velocity of alcohol is 1.0-2.0h-1. The alcohol can be anhydrous alcohol or an aqueous solution of alcohol, with a water content of 1.0% to 10% (by weight); the reaction temperature is preferably 220 to 260° C.; the reaction is carried out at normal pressure.

[0008] The preparation of esters by dehydrogenation condensation of alcohols catalyzed by multiphase supported silica-indium oxide catalysts has the following characteristics: (1) The introduction of active metals promotes the dehydrogenation of alcohols; (2) With silica as the matrix, the physical isolation of silica effectively controls the particle size of indium oxide particles at high temperatures, forming unsaturated indium oxide nano-islands, increasing the concentration of Lewis acid sites, promoting the condensation of aldehydes and alcohols to form hemiacetals, and then undergoing dehydrogenation reactions to obtain ester products, thereby obtaining a highly active and stable catalytic system. (3) Through the physical isolation of silica, active metal species are dispersed to avoid sintering of metals during the reaction and improve stability, while the dehydrogenation activity of metals is partially inhibited to avoid excessive dehydrogenation, thereby improving the selectivity of dehydrogenation. The composition control and content of each component of the multiphase supported silica-indium oxide catalyst are crucial factors.

[0009] The advantages of this method are: (1) The multiphase supported silicon oxide-indium oxide catalyst catalyzes the dehydrogenation condensation of ethanol to produce ethyl acetate. The catalyst preparation is simple and the catalyst catalyzes the reaction efficiently. The catalyst activation and regeneration can be completed by simple roasting and reduction operations. (2) The process of preparing esters by catalyzing the dehydrogenation condensation of alcohols by this catalytic system shows certain advantages, with the selectivity of the target product as high as 96%, the conversion rate as high as 80%, and the simultaneous co-production of hydrogen. DETAILED DESCRIPTION

[0010] In order to further explain the present invention in detail, several specific implementation cases are given below, but the present invention is not limited to these embodiments.

[0011] The reaction is carried out in a fixed bed reactor, and the reaction tube is filled with a catalyst and then placed in the fixed bed reactor;

[0012] Example 1

[0013] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0014] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0015] Example 2

[0016] 1.0wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 1.0wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0017] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0018] Example 3

[0019] 10wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 10wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0020] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0021] Example 4

[0022] 5wt%Fe-0.5%Ce / 25wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 25wt% In 2 O 3 -SiO 2catalyst.

[0023] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0024] Example 5

[0025] 5wt%Fe-0.5%Ce / 15wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 15wt% In 2 O 3 -SiO 2 catalyst.

[0026] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0027] Example 6

[0028] 5wt%Fe-1.5%Zr / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Zr were introduced by impregnation method: a certain amount of 10mmol / L ferric nitrate aqueous solution and zirconium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-1.5Zr / 30wt% In 2 O 3 -SiO 2 catalyst.

[0029] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0030] Example 7

[0031] 5wt%Fe-3.5%La / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and La were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and lanthanum nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-3.5La / 30wt% In 2 O 3 -SiO 2catalyst.

[0032] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0033] Example 8

[0034] 5wt%Fe-5.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-5.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0035] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0036] Example 9

[0037] 5wt%Fe-7.5%Al / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-7.5Al / 30wt% In 2 O 3 -SiO 2 catalyst.

[0038] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0039] Example 10

[0040] 5wt%Cu-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Cu and Ce were introduced by impregnation method: a certain amount of 10mmol / L copper nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Cu-0.5Ce / 30wt% In 2 O 3 -SiO 2catalyst.

[0041] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0042] Embodiment 11

[0043] 5wt%Zn-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Zn and Ce were introduced by impregnation method: a certain amount of 10mmol / L zinc nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Zn-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0044] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0045] Example 12

[0046] 5wt%Ni-0.5%Ce / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Ni and Ce were introduced by impregnation method: a certain amount of 10mmol / L nickel nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Ni-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0047] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0048] Embodiment 13

[0049] 5wt%Ru-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Ru and Ce were introduced by impregnation method: a certain amount of 10 mmol / L ruthenium trichloride aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2 g of the above 30 wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt%Ru-0.5Ce / 30wt%In 2 O 3 -SiO 2catalyst.

[0050] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0051] Embodiment 14

[0052] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0053] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0054] Embodiment 15

[0055] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0056] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 240°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0057] Example 16

[0058] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2catalyst.

[0059] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 220°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0060] Embodiment 17

[0061] The used catalyst in Example 1 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed layer. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0062] Embodiment 18

[0063] The catalyst used in Example 17 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed layer. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 8 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0064] Embodiment 19

[0065] The catalyst used in Example 18 was collected and calcined in a muffle furnace at 500°C for 4h, reduced with hydrogen at 300°C for 1h, and filled into a reaction tube with a 15cm bed. The raw material was 5% ethanol aqueous solution, and the mass space velocity was 1.5h -1 The reaction was carried out at 230°C. After 10 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0066] Embodiment 20

[0067] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0068] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was butanol and the mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of butanol and the selectivity of butyl butyrate are shown in Table 1.

[0069] Embodiment 21

[0070] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0071] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was n-hexanol and the mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of n-hexanol and the selectivity of hexyl hexanoate are shown in Table 1.

[0072] Embodiment 22

[0073] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0074] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was octanol and the mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of octanol and the selectivity of ester are shown in Table 1.

[0075] Embodiment 23

[0076] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0077] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was heptanol and the mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of heptanol and the selectivity of ester are shown in Appendix 1.

[0078] Embodiment 24

[0079] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0080] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 10% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0081] Embodiment 25

[0082] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0083] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 0.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0084] Embodiment 26

[0085] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2catalyst.

[0086] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 3.0 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0087] Embodiment 27

[0088] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0089] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 10 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0090] Embodiment 28

[0091] 5wt%Fe-0.5%Ce / 30wt%In 2 O 3 -SiO 2Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / 30wt% In 2 O 3 -SiO 2 catalyst.

[0092] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 20 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 230°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0093] Comparative Example 1

[0094] 5wt%Fe-0.5%Ce / In 2 O 3 Preparation of catalyst: Weigh 30g of hydrated indium nitrate and dissolve it in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH to 8, continue stirring for 4 hours, filter, wash three times with water, and evaporate to dryness at 100°C to obtain In 2 O 3 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L iron nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / In 2 O 3 catalyst.

[0095] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0096] Comparative Example 2

[0097] 5wt%Fe-0.5%Ce / SiO 2 Preparation of catalyst: Weigh 30g of ethyl orthosilicate and disperse it in 500mL of ethanol aqueous solution, with the volume ratio of ethanol to water being 1:1; add sodium hydroxide aqueous solution (1M) dropwise into the above solution under stirring, adjust the pH to 8, continue stirring for 4 hours, filter, wash with water three times, and evaporate to dryness at 100°C to obtain SiO 2 ; Fe and Ce were introduced by impregnation method: a certain amount of 10mmol / L ferric nitrate aqueous solution and cerium nitrate aqueous solution were co-impregnated, stirred at room temperature, and 2g of the above SiO 2 The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 5wt% Fe-0.5Ce / SiO 2 catalyst.

[0098] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0099] Comparative Example 3

[0100] 0.5%Ce / 30wt%In 2 O 3 -SiO 2 Preparation of catalyst: Weigh 5g of hydrated indium nitrate and a certain amount of tetraethyl orthosilicate, dissolve in 500mL of ethanol aqueous solution, the volume ratio of ethanol to water is 1:1; add sodium hydroxide aqueous solution (1M) dropwise to the above solution under stirring, adjust pH=8, continue stirring for 4 hours, filter, wash three times with water, evaporate to dryness at 100°C, and obtain 30wt% In 2 O 3 -SiO 2 ; Ce was introduced by impregnation method: a certain amount of 10mmol / L cerium nitrate aqueous solution was impregnated, stirred at room temperature, and 2g of the above 30wt% In 2 O 3 -SiO 2The matrix was stirred for 4 hours, evaporated to dryness at 100°C, and calcined at 400°C for 4 hours to obtain 0.5Ce / 30wt%In 2 O 3 -SiO 2 catalyst.

[0101] The catalyst with a mesh size of 14-25 was sieved and filled into the reaction tube. The bed layer was 15 cm. The raw material was 5% ethanol aqueous solution. The mass space velocity was 1.5 h -1 The reaction was carried out at 260°C. After 2 hours of reaction, samples were taken for chromatographic analysis. The conversion rate of ethanol and the selectivity of ethyl acetate are shown in Table 1.

[0102] Appendix 1. Reaction results of alcohol dehydrogenation condensation to prepare esters catalyzed by heterogeneous supported silicon oxide-indium oxide catalyst

[0103]

[0104]

[0105] The results show that the composition and content of each component of the supported silica-indium oxide composite catalyst are key factors affecting the reaction effect. The synergistic mechanism of the appropriate metal content as the dehydrogenation site and the silica-dispersed indium oxide condensation site is the key to achieving high selectivity catalysis. The lack of acidic sites or the silica dispersion medium or inappropriate ratio will cause a mismatch in the reaction rate, resulting in a significant decrease in the selectivity of the target product ethyl acetate. In addition, the addition of additives, reaction temperature, space velocity and other conditions also affect the reaction effect.

Claims

1. A method for preparing an ester, characterized in that: The ester preparation process is as follows: alcohol is used as a raw material, a reaction is carried out in a fixed bed reactor, a multiphase supported silicon oxide-indium oxide catalyst is filled in a reaction tube and the reaction tube is placed in the fixed bed reactor, and the reaction temperature is 220-300°C; The multiphase supported silica-indium oxide catalyst is composed of active metal, silica, indium oxide and a catalyst promoter, or is composed of active metal, silica and indium oxide; The active metal is one, two or more of Cu, Fe, Zn, Ni and Ru; The active metal content is 1.5% to 10% by weight; the indium oxide content is 10-35% by weight; the catalyst additive content is ≤10% by weight; The heterogeneous supported silica-indium oxide catalyst, the catalyst promoter is one, two or more of Zr, La and Ce; The alcohol is one, two or more of ethanol, butanol, n-hexanol, octanol and heptanol; The supported silica - indium oxide composite catalyst, the silica - indium oxide carrier is prepared by co-hydrolysis of an organosilane and / or tetraethyl orthosilicate with an indium precursor salt, the hydrolysis is carried out at room temperature, the concentration of the indium salt is 0.1 ~ 1.1 mol / L; the concentration of the organosilane and / or tetraethyl orthosilicate is: 1 ~ 10 mol / L; pH: 8 ~ 11; The active metals and additives are introduced by impregnation.

2. The preparation method according to claim 1, characterized in that: The multiphase supported silica-indium oxide catalyst has an active metal content of 3%-8% by weight, an indium oxide content of 20%-35% by weight, and a catalyst promoter content of 3%-5% by weight.

3. The preparation method according to claim 1, characterized in that: The feed mass space velocity of alcohol is 1.0~3.0 h -1 .

4. The preparation method according to claim 1, characterized in that: The feed mass space velocity of alcohol is 1.0~2.0 h -1 .

5. The preparation method according to claim 1, characterized in that: The alcohol is anhydrous alcohol or an aqueous solution of alcohol, and the water content is 1.0% to 10% by weight; The reaction temperature is 220-260°C; the reaction is carried out under normal pressure.

Citation Information

Patent Citations

  • Catalyst for carboxylic acid ester production, method for producing the same, and method for producing carboxylic acid ester

    WO2009022544A1